2017
DOI: 10.1371/journal.pone.0169414
|View full text |Cite
|
Sign up to set email alerts
|

An Improved and Secure Anonymous Biometric-Based User Authentication with Key Agreement Scheme for the Integrated EPR Information System

Abstract: Nowadays, many hospitals and medical institutes employ an authentication protocol within electronic patient records (EPR) services in order to provide protected electronic transactions in e-medicine systems. In order to establish efficient and robust health care services, numerous studies have been carried out on authentication protocols. Recently, Li et al. proposed a user authenticated key agreement scheme according to EPR information systems, arguing that their scheme is able to resist various types of atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…In this section, we compare recent electronic medical solutions by their computational and communication costs. Comparisons of Wen et al [7], Li et al [12], Jung et al [13], Wu et al [17], Lin et al [28], Lee et al [29], and our method are illustrated in Table 2, a performance comparison table, where T H denotes the execution time of the biometric-hash function operation, T h denotes the execution time of the one-way hash function operation, T xor denotes the execution time of the Exclusive-OR (short for XOR) operation, T M denotes the execution time of multiplication operations, and T qr denotes the execution time of computing a square root modulo n. T xor , T h , and T H belong to lightweight operations. According to the description of [15,23], the calculation of the XOR operation is negligible, and the T h ≈ T H time cost is similar.…”
Section: Performance Comparisonsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this section, we compare recent electronic medical solutions by their computational and communication costs. Comparisons of Wen et al [7], Li et al [12], Jung et al [13], Wu et al [17], Lin et al [28], Lee et al [29], and our method are illustrated in Table 2, a performance comparison table, where T H denotes the execution time of the biometric-hash function operation, T h denotes the execution time of the one-way hash function operation, T xor denotes the execution time of the Exclusive-OR (short for XOR) operation, T M denotes the execution time of multiplication operations, and T qr denotes the execution time of computing a square root modulo n. T xor , T h , and T H belong to lightweight operations. According to the description of [15,23], the calculation of the XOR operation is negligible, and the T h ≈ T H time cost is similar.…”
Section: Performance Comparisonsmentioning
confidence: 96%
“…Alternatively, in the case of offline processing, a zero-knowledge information exchange key agreement was performed through the public network [11]. In the case of the key agreement mechanism, many scholars had proposed related agreements [8,[11][12][13][14][15]. In 2002, using fingerprints as passwords and using a remote login authentication through smart cards and biometrics were common [9].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They used an ID‐based signature and encryption to contract an anonymously key agreement scheme. Jung et al first mentioned the security flaws of Li et al's scheme and showed that this is not resisted against password guessing and spoofing attack also does not achieve password verification. Doshi et al proposed a crucial password‐based agreement protocol for Internet of Things (IoT) environment.…”
Section: Introductionmentioning
confidence: 99%
“…They mentioned that the presented protocol accomplishes smart meter security and SK‐security under the CK‐adversary model. Lee et al mentioned some low flows in Jung et al and showed that it fails to ensure user anonymity. Moreover, they proposed a biometric‐based key agreement scheme for a DRM system.…”
Section: Introductionmentioning
confidence: 99%